Analysis of the Influence of Innovation Capability, Digital Competence, and Digital Transformation on the Performance of Culinary SMEs in Medan City with Self-Directed Learning as an Intervening Variable - Idzni, Amajida Nurul; Dalimunthe, Ritha F; Absah, Yeni (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes the influence of innovation capability, digital competence, and digital transformation on the performance of culinary SMEs in Medan City with self-directed learning as an intervening variable. Using a quantitative approach, 230 samples of culinary SMEs were selected through multistage sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with Partial Least Square (PLS). The results show that innovation capability, digital competence, and digital transformation have a positive and significant effect on self-directed learning and SME performance. Self-directed learning mediates the influence of digital competence and digital transformation on the performance of SMEs, but does not mediate the influence of innovation capability. This research provides recommendations to improve the performance of culinary SMEs through the development of innovation capabilities, digital competencies, and digital transformation.